DOUBLE BOOTSTRAP CONTROL CHART FOR MONITORING SUKUK VOLATILITY AT BURSA MALAYSIA (Jurnal Teknologi (Sciences & Engineering), 2017)
The bootstrap approach on control limit has provided a solution in solving uncertainty estimation problem in control chart performance. However, the limitation of this standard chart has shown to be less efficient and invalidation at certain magnitude shift, especially the monitored sample data is assumed from skewed family distribution. Thus, in this study, a double bootstrap base-model and its control limit is developed in order to improve the efficiency and decrease the invalidation chart performance. In order to test the performance of proposed model, a simulation study using Average Run Length (ARL) and Type II Error rate were implemented. The result has shown that the proposed chart is sensitive and effective in detecting the shift process for small and medium size of skewed sample data. Also, it has found that the proposed chart shown to has better performance on large magnitude shift. The performance of the proposed model was investigated further using sukuk volatility data at Bursa Malaysia. The result revealed that the double bootstrap control chart is sensitive to small shifts process when it can detect changes in the volatility faster. In other words, it is efficient in monitoring the shifts process. Thus, the proposed model could help the traders in making a new decision, for example, either save/hold for a certain period, sell or buy the sukuk certificate.Â Â